أثر تطبيق الادارة الاستراتيجية على تحسين اداء العاملين: (دراسة حالة مصنع سكر عسلاية - 2022م) - د. كمال أحمد محمد عبدالله, (White Nile Journal for Studies and Research, 2023)
The problem of the study was to answer the following question: what the impact of strategic management on improving the performance of employees? The study aimed to study the concept and importance of strategic planning and strategic management and to identify the extent of application and practice of strategic management in the Asalaya sugar factory and to identify the problems and challenges facing the sugar industry in the Asalaya sugar factory. The study used the descriptive analytical approach. The study assumed the following hypotheses: There is a statistically significant relationship between strategic planning and improving the performance of employees. There is a statistically significant relationship between implementing the strategy and improving the performance of employees. The most important findings of the study: The factory is interested in the strategy that suits its financial capabilities and is keen to communicate its message to all employees. The participation of employees in formulating the strategy in the factory is weak. The most important recommendations are: There is a shortcoming and lack of training courses in the field of strategic management, so it is necessary to intensify training courses in the field of strategic management. The company must provide the material, human and technical capabilities required to implement the strategic plan. Keywords : strategic management, the strategic plan , the performance of employees , training , technical